Improvement of Type 2 Diabetes Mellitus in Obese and Non-Obese Patients after the Duodenal Switch Operation - M. Frenken; E. Y. Cho; W. K. Karcz; J. Grueneberger; S. Kuesters (Journal of Obesity)
Introduction. Type 2 diabetes mellitus (T2DM) is one of the most important obesity-related comorbidities. This study was undertaken to characterise the effect of the biliopancreatic diversion with duodenal switch (BPD-DS) in morbidly obese and nonmorbidly obese diabetic patients. Methods. Outcome of 74 obese diabetic patients after BPD-DS and 16 non-obese diabetic patients after BPD or gastric bypass surgery was evaluated. Insulin usage, HbA1c-levels, and index of HOMA-IR (homeostasis model assessment of insulin resistence) were measured. Results. A substantial fraction of patients is free of insulin and shows an improved insulin sensitivity early after the operation, another fraction gets free of insulin in a 12-month period after the operation and a small fraction of long-term insulin users will not get free of insulin but nevertheless shows an improved metabolic status (less insulin needed, normal HbA1c-levels). Conclusion. BPD-DS leads to an improvement of T2DM in obese and non-obese patients. Nevertheless, more data is needed to clarify indications and mechanisms of action and to adjust our operation techniques to the needs of non-obese diabetic patients.